Vochysiaceae: secondary metabolites, ethnopharmacology and pharmacological potential - Carnevale Neto, Fausto [UNESP]; Pilon, Alan Cesar [UNESP]; Siqueira Silva, Dulce Helena [UNESP]; Bolzani, Vanderlan da Silva [UNESP]; Castro-Gamboa, Ian [UNESP] (Springer, 2011)
Many Vochysiaceae species, in special Qualea and Vochysia genera, are widely used in folk medicine to treat several diseases. This review describes some aspects of their ethnopharmacology potential, biological activity and the secondary metabolites reported so far for Vochysiaceae. The chemical constituents of this family include triterpenoids, steroids and polyphenols like flavonoids and ellagic acid derivatives.
Keywords: Ellagic acid derivatives; Ethnopharmacology; Flavonoids; Triterpenoids; Vochysiaceae